Bacillus velezensis NDB mitigates Aeromonas hydrophila-induced enteritis in black sea bream (Acanthopagrus schlegelii) by enhancing intestinal immunity and modulating gut microbiota - Zhang, Zhixuan; Wang, Ze; Wang, Zhonghua; Yi, Haojia; Su, Xiurong; Wang, Rixin; Ming, Tinghong; Xu, Jiajie (Frontiers in Microbiology, 2025)
Aeromonas hydrophila-induced enteritis presents a significant challenge to the intensive aquaculture of black sea bream (Acanthopagrus schlegelii). Studies have shown that probiotic supplementation provides a promising alternative to conventional antibiotic applications for disease prevention in aquaculture. In this study, we investigated the protective effects of dietary supplementation with Bacillus velezensis NDB on the growth, immunity, and intestinal microbiota of black sea bream against A. hydrophila-induced intestinal damage. A total of one hundred and eight black sea bream fingerlings (initial body weight of 9.44 ± 0.03 g) were randomly assigned to three groups (total of nine tanks, twelve fish per tank): a control group (CON, normal diet), an infected group (AH, normal diet for 28 days followed by A. hydrophila infection at 1.0 × 107 CFU/mL), and a probiotic-treated group (AH+NDB, diet supplemented with 1.43 × 108 CFU/g B. velezensis NDB for 28 days, followed by A. hydrophila infection at 1.0 × 107 CFU/mL). The results showed that the weight gain rate in the AH+NDB group was 139.44 ± 48.61%, which was significantly higher than that in the CN (126.81 ± 43.48%) and AH (132.48 ± 63.54%) groups. The pathological symptoms of black sea bream induced by A. hydrophila, including gill and abdominal hemorrhage, villus deformation, and inflammatory infiltration, were alleviated in the AH+NDB group. Histological and biochemical analyses showed the dietary supplementation of B. velezensis NDB enhanced antioxidant enzyme activities (SOD and CAT) and reduced lipid peroxidation (MDA) in the AH+NDB group. Compared to the AH group, the AH+NDB group exhibited significantly upregulated expression levels of anti-inflammatory markers (il10 and tgf-β), and significantly downregulated levels of pro-inflammatory cytokines (il1, tnf-α, and ifng). Moreover, dietary supplementation with B. velezensis NDB increased the abundance of beneficial genera (e.g., Bacillus and Ruegeria), and decreased the abundance of opportunistic pathogenic genera (e.g., Aeromonas and Vibrio), thus enhancing the carbohydrate/amino acid biosynthesis and promoting the nucleoside and nucleotide biosynthesis to alleviate A. hydrophila-induced enteritis. Collectively, the study demonstrated that dietary supplementation with B. velezensis NDB can effectively promote growth performance and enhances immune function in black sea bream, thereby providing significant benefits for fish culture.